Corporate Taxation in the U.S. and Canada – A Comparative Analysis - Elif Gürlek (Junior Management Science (JUMS), 2021)
As the degree of global trade integration increased, corporate taxation became a border-crossing matter that obliged governments to reassess the tax attractiveness of their jurisdictions. The U.S. and Canada are two major players of today's trade landscape and the corporate tax environment of these two countries impact MNEs investment decisions. Historically, Canada offered a more favourable tax environment compared to its neighbour. However, the U.S. tax reform, TCJA, challenged Canada's tax attractiveness. This paper aims to assess the similarities and differences of both countries' tax systems after the tax reform based on the tax attractiveness criteria. Following, the paper examines lessons that can be derived for Canada to regain its strong position in the global tax attractiveness scenery. The U.S. and Canada have the potential to set an example for lawmakers and show that it is possible to create a corporate taxation environment that preserves governments' interest whilst creating attractive taxation policies in the eye of MNEs.
Keywords: 650; Corporate taxation; United States; Canada; tax attractiveness; Tax Cuts and Jobs Act